RELIGIOUS AND MORAL EDUCATION (RME) TEACHERS’ TECHNOLOGICAL CONTENT KNOWLEDGE BASE IMPACT ON STUDENTS IN JUNIOR HIGH SCHOOLS IN GHANA - BORDOH, PRO.ANTHONY (International Journal of Multidisciplinary Research and Studies, 2019)
Religious and Moral Education (RME) is an indispensable subject in the Ghanaian educational enterprise. The study was conducted to find out teachers’ technological content knowledge in the teaching of Religious and Moral Education (RME) in Aowin municipality in the Western Region of Ghana. The descriptive survey was the design for the study. The population included all (RME) teachers in the Aowin municipality. However, a sample population of 33 RME teachers was used for the study through simple random sampling technique. The data was organized into tables, frequencies, percentages and means in line with the research questions which guided the study. The study revealed that teachers generally had the technological competence in teaching RME but these competencies were mostly manifested in their use of lower levels of technology. Teachers also possessed adequate content knowledge of RME which they appropriately displayed in class. However, the teachers had little knowledge in the Islamic aspect as compared to the other aspects of RME. The study recommended that the Ghana Education Service organize intensive In-service training for teachers on the need to integrate technology in teaching RME. It also recommended that teachers read more on the Islamic aspect of RME in order to have adequate knowledge on it. It was finally recommended that the teacher preparation programmer should provide opportunities for potential teachers to learn more skills in integrating technology and content skills in teaching. Consequently, supervisors in basic schools including head teachers, circuit supervisors should strengthen their supervisory roles on what teachers do in the classroom rather than concentrating on what teachers say they can do or are doing.